Cutting Edge: Acute Lung Allograft Rejection Is Independent of Secondary Lymphoid Organs() - Gelman, Andrew E. (2009)
It is the prevailing view that adaptive immune responses are initiated in secondary lymphoid organs. Studies using alymphoplastic mice have shown that secondary lymphoid organs are essential to initiate allograft rejection of skin, heart, and small bowel. The high immunogenicity of lungs is well recognized and allograft rejection remains a major contributing factor to poor outcomes after lung transplantation. We show in this study that alloreactive T cells are initially primed within lung allografts and not in secondary lymphoid organs following transplantation. In contrast to other organs, lungs are acutely rejected in the absence of secondary lymphoid organs. Two-photon microscopy revealed that recipient T cells cluster predominantly around lung-resident, donor-derived CD11c(+) cells early after engraftment. These findings demonstrate for the first time that alloimmune responses following lung transplantation are initiated in the graft itself and therefore identify a novel, potentially clinically relevant mechanism of lung allograft rejection.